Effective teaching and motivation: Application of self-determination theory - Perlman, Dana J. (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
Developing quality and effective future teachers is a cornerstone of all teacher-education programs. An area of inquiry that has been identified as influential within the teacher development process is the concept of motivation. Therefore, the purpose of this study was to examine if there were differences between elements of effective teaching based on preservice teachers (PTs) motivation toward teaching. 68 (Male=44; Female=24) undergraduate Physical and Health Education PTs were recruited within this study. PT data were collected on their motivation toward teaching and elements of effective teaching. Results indicated that motivation was associated with elements of effective teaching.